Francisella-Like Endosymbiont Detected in Haemaphysalis Ticks (Acari: Ixodidae) From the Republic of Korea. Issue 6 (12th July 2017) - Takhampunya, Ratree; Kim, Heung-Chul; Chong, Sung-Tae; Korkusol, Achareeya; Tippayachai, Bousaraporn; Davidson, Silas A; Petersen, Jeannine M; Klein, Terry A
Abstract: A total of 6, 255 ticks belonging to three genera and six species ( Haemaphysalis flava Neumann, Haemaphysalis longicornis Neumann, Haemaphysalis phasiana Saito, Ixodes nipponensis Kitaoka & Saito, Ixodes persulcatus Schulze, and Amblyomma testudinarium Koch) collected from May–August, 2013, at four southwestern provinces in the Republic of Korea (ROK) were submitted to the Armed Forces Research Institute of Medical Sciences and assayed for selected tick-borne pathogens. One pool each of H. flava and H. phasiana was positive by PCR and sequencing for a Francisella -like endosymbiont, while all pools were negative for Francisella tularensis, the causative agent of tularemia.